2018
DOI: 10.1111/ene.13800
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improvements in patients with cervical dystonia following treatment with a liquid formulation of abobotulinumtoxinA (Dysport®)

Abstract: Repeat ASI injections are similarly effective to abobotulinumtoxinA in improving patient-reported outcomes of health-related quality of life. Positive correlations were found between TWSTRS total and domain scores and CDIP-58 total and domain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
2
Order By: Relevance
“…Furthermore, 27% of the current study indicated that they had a history of difficulties with their mental health, supporting a recent study which found that 23% had a history of clinical diagnosis of mood disorder prior to CD onset and 39% reported having one at any stage (Ndukwe et al, 2020a , 2020b ). With regard to HRQoL, the current cohort reported a CDIP-58 score of 35.83, which is substantially lower than a recent multicentre randomised controlled trial ( M = 59.1; Simonetta-Moreau et al, 2019 ), which suggests that the current group of pwCD experience a higher HRQoL.…”
Section: Discussioncontrasting
confidence: 84%
“…Furthermore, 27% of the current study indicated that they had a history of difficulties with their mental health, supporting a recent study which found that 23% had a history of clinical diagnosis of mood disorder prior to CD onset and 39% reported having one at any stage (Ndukwe et al, 2020a , 2020b ). With regard to HRQoL, the current cohort reported a CDIP-58 score of 35.83, which is substantially lower than a recent multicentre randomised controlled trial ( M = 59.1; Simonetta-Moreau et al, 2019 ), which suggests that the current group of pwCD experience a higher HRQoL.…”
Section: Discussioncontrasting
confidence: 84%
“…The QoL measure (CIDIP-58), another measure with no pre-defined thresholds, is lower in our patients than in other reports in the literature [23] , [20] , again possibly indicating a milder form of disease. In our correlation analysis, we noted no clear significant correlations between mood, cognitive and motor scores.…”
Section: Discussioncontrasting
confidence: 77%
“…BoNT-A toxin causes muscle paralysis by inhibiting the peripheral cholinergic nerves from releasing acetycholine which triggers contraction of muscles. Several studies have shown that BoNT-A therapy increases free movement range, alleviates pain and improves quality of life for CD patients [6][7][8][9]. A considerable amount of studies have confirmed that BoNT-A is effective and well-tolerated in patients with CD [3].…”
Section: Introductionmentioning
confidence: 99%